Prioritise propensity: a multimethod analysis of peer influence and school-based aggression - Kennedy, Laura (Deviant behavior, 2024)
This study examines the situational role of aggressive peers in the explanation of school-based aggression. Using data from the multimethod Peer Relations and Social Behavior (PEERS) study, it tests hypotheses derived from Situational Action Theory (SAT) to investigate whether the effect of aggressive peers is greater for high propensity adolescents. The PEERS study used a cross-sectional survey followed by adapted Space-Time Budget (STB) interviews with a randomly selected subsample of participants. This paper presents situational analyses of STB data alongside additive analyses of survey data to demonstrate both situational convergence and statistical dependence. Results showed that the effect of aggressive peers was greatest amongst adolescents with high aggression-relevant propensity (i.e. weak morality and a poor ability to exercise self-control). Whilst high propensity adolescents were situationally vulnerable to the influence of aggressive peers, low propensity adolescents were situationally resistant to criminogenic peer effects. These findings suggest that targeting aggression-relevant propensity may be more fundamental than reducing exposure to aggressive peers for preventing aggressive behavior in schools. The theoretical, methodological, and empirical contributions in this study can be applied to advance future research on peer influence, aggression, and SAT.